The Implementation of Linear Program in Determining Product Combinations to Achieve Optimal Profits in Nganjuk “Syukur” Tile Home Industry - Sinollah, Sinollah (Universitas Ciputra Surabaya, 2020)
The objective achieved through this research is to study the application of linear programming in determining the combination of products that can produce optimal profits in the Nganjuk